2009
DOI: 10.1007/s10666-009-9196-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan

Abstract: This study designs a multipurpose urban shallow artificial lake, including water supply, flood detention, and water environment preservation. It is expected to not only preserve a healthy water environment but to also retain water conservation and flood detention. This study adopts system dynamics (SD) to analyze the relationship between different purposes of water resources utilization. Furthermore, different operation strategies effects can be simulated by SD through a proposed urban multipurpose shallow art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Chu et al studied application of system dynamics on shallow lakes in Taiwan. They have concluded that SD can help us to predict and understand temporally in sequential planning for water supply and environmental protection (Chu et al 2010). Numerous studies have focused on the modeling of WSPs (Benedetti et al 2010; Craggs et al 2004; Rivas et al 2008; Senzia et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al studied application of system dynamics on shallow lakes in Taiwan. They have concluded that SD can help us to predict and understand temporally in sequential planning for water supply and environmental protection (Chu et al 2010). Numerous studies have focused on the modeling of WSPs (Benedetti et al 2010; Craggs et al 2004; Rivas et al 2008; Senzia et al 2002).…”
Section: Introductionmentioning
confidence: 99%